Optimal mental health for achieving health security in Nigeria: a strategic blueprint (2019)
Objectives: Optimal mental health refers to ‘a state of well-being in which the individual realizes his or her abilities, can cope with the normal stresses of life, can work productively and fruitfully, and is able to make contributions to his or her own community’. As such, the catchphrase ‘No health without mental health’ is not just a slogan but an acknowledgement of the importance of mental health in the drive to improve overall wellbeing and productive participation in community and economic activities. Methods: We combined an overview of current literature with opinions of key experts from different sub specialties of mental health practice and present an analysis of the Strengths, Weaknesses, Opportunities and Threats (SWOT) to optimal mental health as a strategy to attaining health security in Nigeria by 2050. We also offered recommendations for feasible strategies to optimize mental health. Results: There is poor mental health coverage in Nigeria, with over 80% of persons coping with mental health problems remaining untreated in their lifetime. Also, only about 3% of the National health budget is allocated to mental health and this is mostly focused on large psychiatric institutions to the exclusion of primary health care (PHC) services. Conclusions: In recognition of the critical role of optimal mental health to global development, the Sustainable Development Goals (SDGs) has mental health firmly covered in its third goal, ‘Health and Well-being’. The SDGs further envision a better world in which, in tandem with the WHO definition of health, “physical, mental and social wellbeing are assured”. Thus, the identification and implementation of strategies to promote optimal mental health for all Nigerians is vital for ensuring health security and national development.